Kreativitas Belajar dan Efikasi Diri Akademik sebagai Faktor Pemahaman Konsep Materi Interaksi Sosial - Lina Melati; Jenny Indrastoeti Siti Poerwanti; Sukarno Sukarno (Universitas Sebelas Maret, 2026)
Conceptual understanding of social interaction in IPAS learning at the elementary school level requires students to integrate and apply concepts meaningfully. The low level of conceptual understanding observed in the field is suspected to be closely related to learning creativity and academic self-efficacy, which have not yet been studied in an integrated manner. This study aims to examine the relationship between learning creativity and academic self-efficacy and conceptual understanding of social interaction material, both partially and simultaneously, among fifth-grade students in public elementary schools across the Serengan District of Surakarta. The study employed a quantitative approach with a correlational design. A sample of 123 students was selected through cluster random sampling from four schools: SDN Kratonan, SDN Kawatan, SDN Slembaran, and SDN Joyotakan. Data were collected using a Likert scale questionnaire and multiple-choice tests, then analyzed using simple and multiple correlation tests. The results showed that learning creativity (r = 0.375) and academic self-efficacy (r = 0.476) each had a positive and significant relationship with conceptual understanding, and simultaneously, both produced a correlation coefficient of 0.584 (Sig. = 0.000). The stronger simultaneous relationship compared to the partial relationships demonstrates that learning creativity and academic self-efficacy complement each other in fostering deep and meaningful conceptual understanding. These findings imply that teachers need to design learning experiences that simultaneously encourage learning creativity and build academic self-efficacy as a strategy for enhancing conceptual understanding in a more effective and meaningful way.